Community (mis)participation in Urban Green Space restoration: A case of the Wilds Nature Reserve, Johannesburg - Marere, Nozipho P. (University of the Witwatersrand, Johannesburg, 2024)
There is a notable rise in privatized urbanism in South Africa, a trend which re/produces urban inequalities. This research sought to determine whether community involvement in urban green space restoration follows the same trend of private urbanism resulting in an apartheid legacy of separate development, exclusion and segregation. The research followed the qualitative case study approach. Data collection instruments used were semi-structured interviews, with a sample size of twenty-two individuals, selected through a combination of convenience and purposive sampling. Participant observations, which were done over a period of three months, also supplemented by photographs of biophysical elements of note highlighted by participants through transect walks. Findings from this research established that community participation at the Wilds is informal. Challenges in the way of a working and effective public-private partnership include power dynamics, lack of trust and bureaucracy. However, in the absence of a formal working relationship, a novel form of co-production occurs resulting in spaces of hybrid character. Hybrid spaces are therefore the medium of (re)production of power, privilege, exclusion and inequality. Main groups excluded from participation in restoration include Black people, women and children. Their exclusion is based on social class or income level, level of education and awareness and vulnerability of physical assault and abuse. A recommendation for future research is an exploration of local systems of innovation by young people in Urban Green Space development and management.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Urban Green Space restoration; Wilds Nature Reserve; Johannesburg; SDG-11: Sustainable cities and communities